Proceedings of the 7th ACM Conference on Recommender Systems 2013
DOI: 10.1145/2507157.2508070
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and robustness impacts of power user attacks on collaborative recommender systems

Abstract: Power users, in a Collaborative Filtering (CF) Recommender System (RS) context, are those who can exert considerable influence over the recommendation outcomes presented to other users. RS operators encourage the existence of power user communities and leverage them to help fellow users make informed purchase decisions. Thus, RS research in this area has focused on power user selection and utilization to address challenges such as rating sparsity for new items or users. But, as ever, there remains the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…To be clear, the power user attack in our research is not about having many actual power users collude to mount an attack, rather, it is about being able to generate a set of synthetic power user profiles that, when entered into a RS database, can effectively bias the recommendations. We found that Power User Attacks (PUAs) are able to successfully impact SVD-based and user-based recommenders [16,19,20]; we also confirmed previous research [8,11,20] that item-based systems are fairly robust to attack.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…To be clear, the power user attack in our research is not about having many actual power users collude to mount an attack, rather, it is about being able to generate a set of synthetic power user profiles that, when entered into a RS database, can effectively bias the recommendations. We found that Power User Attacks (PUAs) are able to successfully impact SVD-based and user-based recommenders [16,19,20]; we also confirmed previous research [8,11,20] that item-based systems are fairly robust to attack.…”
Section: Introductionsupporting
confidence: 88%
“…The PUA consists of one or more user profiles containing item ratings (called attack user profiles) that push or nuke a specific item. The PUA demonstrated that influential users can impact recommendations for user-based and SVD-based systems; to a much lesser extent, item-based systems can also be impacted [19,16,20]. These attacks were successful because power users are able to correlate with many non-power users to impact the target item ratings.…”
Section: Related Workmentioning
confidence: 99%
“…12) PUA-AS attack: The top 50 users with the highest Aggregate Similarity scores become the selected set of power users. This method requires at least 5 co-rated items between user u and user v and does not use significance weighting [21]. 13) PUA-ID attack: Based on the In-Degree centrality concept from social network analysis, power users are those who participate in the highest number of neighborhoods.…”
Section: Attack Profiles and Attack Modelsmentioning
confidence: 99%
“…For each user u compute its similarity with every other user v applying significance weighting, then discard all but the top 50 neighbors for each user u. Count the number of similarity scores for each user v and select the top 50 user v's [21]. 14) PUA-NR attack: Power users are the users with the highest number of ratings.…”
Section: Attack Profiles and Attack Modelsmentioning
confidence: 99%
“…These users should represent the interests of the whole population as fully as possible and/or be capable to influence the preferences of others. Such set of users is referred to as seed users or seeds , representative users , influential users (Rashid 2007), power users (Seminario and Wilson 2014) or leaders (Esslimani et al 2013).…”
Section: Cold-start Problem In Collaborative Filteringmentioning
confidence: 99%